Implementasi Quantum Learning Upaya Meningkatkan Keterampilan Menulis Karangan pada Pembelajaran Bahasa Indonesia Kelas III di Sekolah Dasar - Siti Aisah; Ismail Marzuki (STKIP PGRI SITUBONDO, 2023)
Indonesian language learning is a very important and mandatory learning for students throughout Indonesia. Learning Indonesian also leads to writing sentences and words that are in accordance with the rules or EYD. This research was conducted to determine whether the quantum learning method affects the learning process Indonesian especially in grade 3 at UPT SD Negeri 49 Gresik 2023. This study used PTK research. In class action research (PTK) this refers to the theory proposed by Stephen Kemmis and Robin MCTaggart, which uses the spira system. In this PTK model there are 4 stages of the cycle. To obtain results in each cycle, steps will be carried out such as planning, action / observation, reflection. So that research results are obtained in accordance with the desired success indicators. Pre-cycle results (before action is given) obtained an average result of Indonesian learning of 62.7 percentage of 63% of the